Design for environment and design for disassembly practices in Malaysia: a practitioner's perspectives. (1st December 2015) - Raja Ghazilla, Raja Ariffin; Sakundarini, Novita; Taha, Zahari; Abdul-Rashid, Salwa Hanim; Yusoff, Sumiani
Abstract: Design for Environment (DfE) and Design for Disassembly (DfD) have been recognized as an effective sustainable manufacturing approach to reduce environmental impact during product's life cycle. Although Malaysian manufacturers have long demonstrated a strong global market presence, the implementation of DfE and DfD among manufacturers are found lacking. This paper attempts to investigate the current state DfE and DfD implementation and the local driving force in the local Malaysian industry by addressing four research questions (RQ): RQ1 – How do Malaysian designers value the importance of DfE? RQ2 – What are the current approaches used by designers to incorporate environmental issues during product development stage? RQ3 – What difficulties are experienced in the implementation of DfE and DfD in the product development stage? RQ4 – What are the approaches needed to enhance the engagement of DfE and DfD into product design practices? Targeting product designers in Malaysia, a multiple approach using survey and interview is conducted shown that the current state of implementation and awareness within the local industry is fairly low. The soft approach of the local legislation does not contribute much towards seeing a major change in attitude as will be discussed further in the paper. The above two concerns are major challenges that require immediate attention. However, there seems to be growing concern from the industry and the government that pushes the need for options that could leapfrog the current situation. This presents an opportunity for the local research community to come up with various strategies that will be discussed. Finally, the paper proposes a more comprehensive strategy that is tailored to the local business environment in order for the local industry to be capable of maintaining its market presence.